USE OF INDUSTRIAL WASTE WATER IN CONCRETE - Prof. Pranesh chawhan, Akash A.Bhosale ,Harshal Jamsutkar ,Amey Jamsutkar, Ragini Jadhac, Aarti Jadhav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Water is a basic need of living beings. So, everyone should be benefited with quality and quantity water. Oceans hold over 97 percent of the world's water, while freshwater makes up only 3 percent. Moreover, freshwater is not distributed equally across land surfaces, and there are some densely populated nations where freshwater is scarce. On other hand, concrete industry consumes large amount of water in mixing of mortar, mixing of concrete and even in curing which otherwise can be used for drinking purpose. Construction industry is second largest industry in India which consumes major amount of water. Waste water gets mixed with the surface water after discharging it from industries. It tends to reduce the quality of surface water which is sometimes get consumed by humans for drinking purpose. Bad quality of water may affect the health of human beings and aquatic life also. Water shortage is becoming a global issue these days. And more efforts should be made to fix this issue. As a result, using waste water released from various types of companies or sites in the building sector may assist to alleviate the problem of water shortage. This project intends to demonstrate how treated waste water may be used in the construction sector while reducing the environmental impact. While building concrete, waste water collected from dairies, car wash centres, sewage treatment plants, and other locations is utilised as a 100 percent substitute. After casting and curing with oil industry water for 7, 14, and 28 days, cubes are intended to be assessed against compression stress.